Applicability of the International Cytopathology Reporting System of Serous Fluids in a Brazilian City - Santos, Caio Rodrigo dos; Silva, Daniel José Castilho da; Camilo-Júnior, Deolino João; Xavier, José Candido Caldeira [UNESP] (Karger Publishers, 2024)
Introduction: The International Academy of Cytology and the American Society of Cytopathology developed the International System of Serous Fluid Cytopathology (TIS) to standardize cytological reports. Effusions in pleural, peritoneal, and pericardial cavities are valuable sources of information for medical diagnosis, especially in oncological scenarios. The TIS classification is divided into five categories: nondiagnostic (ND), negative for malignancy (NFM), atypia of uncertain significance (AUS), suspected malignancy (SFM), and malignant (MAL). It facilitates global communication between specialists, aiming for future clinical management guidelines based on malignancy risk assessment. Methods: This quantitative analytical and retrospective study evaluated serous fluids (pleural, pericardial, and peritoneal) sent to the Instituto de Patologia de AraÃ§atuba (IPAT), SÃ£o Paulo, Brazil, from public and private hospitals between January 2017 and December 2022. Epidemiological and clinical data were collected from institutional files, including biopsies and immunohistochemical results. Results: The study included 719 patients with 763 serous fluid samples (pericardial, pleural, and peritoneal) analyzed over 6 years. The majority of samples were from pleural effusions ( = 438; 57.4%), followed by peritoneal ( = 293; 38.4%) and pericardial effusions ( = 32; 4.2%). Samples were classified using the International Serous Fluid Cytopathology System (TIS), revealing the following distribution: ND (0.41%), NFM (70.30%), AUS (0.95%), SFM (11.90%), and MAL (16.44%). The risk of malignancy calculated for each category was ND 66.67%, NFM 23.39%, AUS 28.57%, SFM 48.28%, and MAL 84.17%. Conclusion: The ROM was out of the interval proposed by the TIS in all categories. These findings suggest the applicability of TIS even outside of the cancer center environment, although the presented ROM frequencies were out of the recommended range.
Keywords: Applicability protocol; Cytopathological diagnosis; Effusions; International system; Serous fluids